Improve the Quality of Life with Magnetically Implant-Supported Overdenture - Darmiaty, Darmiaty; Arfa, Sitti; Machmud, Edy; Habar, Ike Damayanti (Indonesian Journal of Prosthodontic, 2021)
Patient chief complaint: A 50-year-old woman comes to the Dental Hospital Hasanuddin University Makassar with complaints of masticatory disorders because the dentures that have been used for 9 years are loose and wobbly so that they feel painful when used to eat. Patient’s Oral Status: Intra-oral examination revealed the upper and lower jaws the patient is completely edentulous. In the lower jaw is also accompanied by alveolar ridge resorption. Treatment plan: Using an implant-supported overdenture with magnetic retention in the mandible while in the maxilla a conventional denture because there was still a portion of the maxilla that could be used for retention. Detail of therapy: After obtaining the patient's consent and confirming that the patient had no parafunction, two implants were placed on the body of the mandible using a single stage. Right and left implant length 12.0 mm, diameter 4.0 mm. Surface Both the magnet and the attachment guard are coated with titanium nitride (TiN). Clinical significance of therapy: Magnetically implant-supported overdenture can restore masticatory function and restore quality of life